Reduction of Legionella pneumophila and Pseudomonas aeruginosa bacteria in water using gamma irradiation. (October 2022) - Roberts, Rachel; Orr, Robin; Mein, Ian; Paddon, Alex; Cheesewright, Jonathan; Edge, Ruth
Abstract: Pathogenic bacteria found in low levels in natural water systems can present a hazard to human health, such as through contraction of Legionnaires disease, if conditions are favourable for growth and there is potential to create an aerosol. In this study, gamma radiation using a 60 Co source was applied to Legionella pneumophila and Pseudomonas aeruginosa bacteria for 60 min at varying dose rates. All L. pneumophila bacteria were eliminated by irradiation at a dose of 1.86 kGy, and all P. aeruginosa at a dose of 0.70 kGy. Approximate D10 values for L. pneumophila and P. aeruginosa bacteria were 166.3 Gy and 70.9 Gy respectively. Highlights: Legionella pneumophila is sensitive to gamma radiation in water. Pseudomonas aeruginosa is sensitive to gamma radiation in water. Legionella pneumophila is eliminated from water at a dose of 1.86 kGy. Pseudomonas aeruginosa is eliminated from water at a dose of 0.70 kGy.